Modern state of crustal stresses of the Apennine Peninsula and adjacent territories (Central Mediterranean region) - P. A. Savvichev; Yu. L. Rebetsky (Геодинамика и тектонофизика)
This paper discusses models showing the formation of the Central Mediterranean region and the geodynamic setting of the Apennine Peninsula. Cataclastic analysis is used for a repeated reconstruction of the Central Mediterranean region. The catalogue of earthquake focal mechanisms includes 662 events (3.6≤Mb≤6.5) recorded in the study area from 1977 to 2015 (Global CMT, http://www.globalcmt.org; RCMT, http://rcmt2.bo.ingv.it/index.html; Italian CMT dataset, http://rcmt2.bo.ingv.it/Italydataset.html). The reconstruction yielded the directions of principal stresses (including algebraically maximum and minimum ones), locations of domains differing in geodynamic regime, Lode – Nadai coefficients, and orientation of tangential shear stresses acting from the mantle to the crust. By comparing our results to the published data obtained by M.‐L. Zoback’s method, we have identified differences in the orientations of maximum horizontal compression axes at points where the stress ellipsoid takes on its critical values. It is revealed that the strongest earthquakes (M>6) were generated in the areas characterized by the minimum and average relative stress magnitudes.